A direção teatral na América Latina: narrativas de formação na universidade pública - Camacho, Clara Angelica Contreras (2019)
The main objective of this research is to describe with a critical eye: the scope, limitations and challenges faced by academic training in theatre directing in public universities in Latin America, parting from the formative experiences of seven Latin American directors that were trained in the same courses where they teach today. In the search for the identification of the scope, limitations and challenges of training in theatre directing, this thesis reflects on public university in the 21st century in Latin America and the new conceptualizations about the curriculum. It is emphasized that this research is based on the narrative methodology which has experience as its central axis, as an event that transforms. Part of the results of this research shows that training courses in theatre directing have to face the crisis of the public university, which generates a complex panorama, where the courses must defend their fundamentally practical training curricula, and their spaces for creation. Thus, the great challenge of theatre training in directing, is precisely to create mechanisms of dialogical relationship, defending their formative particularities.